The Effect of Return on Asset (ROA) and Net Profit Margin (NPM) on Profit Growth at PT Unilever Indonesia Tbk for the 2005-2023 - Mira Santika Dewi; Nia Kurniasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
Examining the